Pengaruh Program Lumajang Taqwa, Lumajang Cerdas, Lumajang Sehat, Lumajang Makmur dan Lumajang Peduli Terhadap Pencapaian Visi Misi Badan Amil Zakat Nasional Kabupaten Lumajang Tahun 2018 - Achmad Farid; Istiana Umil Mahtum (IQTISHODUNA: Jurnal Ekonomi Islam, 2019)
Data processing is performed using t-test testing techniques. In processing the data the researchers used the help of IBM SPSS statistical computer assistant application program 20. Based on the results of data analysis, the results showed that "there was an influence on the Lumajang taqwa program, Lumajang smart, Lumajang healthy, Lumajang prosperous and Lumajang concerned with the achievement of the vision and mission of the National Amil Zakat Agency (BAZNAS) Lumajang Regency in 2018. Proven t-test results obtained t count Lumajang taqwa = 3.207 with a probability t arithmetic sig. = 0.007, Lumajang smart = 2.526 with t arithmetic sig. = 0.025, Lumajang healthy = 2.511 with t arithmetic sig. = 0.026, Lumajang prosper = 2.506 with t arithmetic sig. = 0.026, and Lumajang cares = 2,200 with t arithmetic sig. = 0.046. So it can be concluded that Lumajang taqwa, Lumajang smart, Lumajang healthy, prosperous Lumajang and Lumajang care have a positive and significant impact on achieving the vision and mission of the BAZNAS Lumajang Regency with a confidence level of 95%. In addition, the correlation coefficient R Lumajang taqwa = 0.665 and included in the interval 0.60 - 0.799, it can be concluded that Lumajang taqwa has a strong influence. 66.5%, intelligent Lumajang = 0.574 and included in the interval 0.40-0.599 in the sense of having a moderate effect that is equal to 57.4%, healthy Lumajang = 0.572 and included in the interval 0.40-0.599 in the sense of having a moderate effect, that is equal to 57.2%, Lumajang prosper = 0.571 and included in the interval 0.40-0.599 in the sense of having a moderate effect that is equal to 57.1, Lumajang caring = 0.521 and included in the interval 0.40-0.599 in the sense of having a moderate effect which is 52.1%.